Increasing the combat readiness and fighting capacity of police officers to act in extreme situations - I. V. Vlasenko; T. V. T. V. Shevchenko (Law and Safety)
The high level of injuries and the number of cases of death of law enforcement officers, especially in extreme situations, require constant and in-depth research in the field of improving the professional abilities of law enforcement officers. There is also no doubt about the practical significance, all units of the National Police from the stage of professional selection to the system of professional training need improvement and a systematic approach to increasing combat readiness and fighting capacity, qualitative changes in the system of professional training. Unfortunately, not every police officer is ready to act in certain difficult and extreme situations.